The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.15694/mep.2020.000159.1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on Medical education and Medical Students. How and when can they return to placements?

Abstract: The defining feature of 2020 will be the early and mid-stages of the covid-19 pandemic, declared by the World Health Organisation on 11 th March. Rapid worldwide exponential spread continues and by 15 April, more than 1 900 000 cases and 123 000 deaths had been reported worldwide (WHO, 2020). Health services have coped to varying degrees. One common feature has been the withdrawal of routine care (Iacobucci, 2020a) and 'non-essential' staff including learners, although many have returned to undertake care role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…The present system under COVID, uses observation of patients by students to acquire the skill needed for practice which is not desirable. It has been reported that in teaching by observation, clinical learners are passive observers which indicates a low yield use of an invaluable resource [19]. As an alternative to hands-on procedures, the institution introduced the use of dummies and mannequins as replacement for live patients.…”
Section: Resultsmentioning
confidence: 99%
“…The present system under COVID, uses observation of patients by students to acquire the skill needed for practice which is not desirable. It has been reported that in teaching by observation, clinical learners are passive observers which indicates a low yield use of an invaluable resource [19]. As an alternative to hands-on procedures, the institution introduced the use of dummies and mannequins as replacement for live patients.…”
Section: Resultsmentioning
confidence: 99%
“…Disruption caused to medical education by the ongoing Covid-19 pandemic has been well described; however, subsequent sequalae such as volunteering and early graduation remain under-discussed. [21][22][23] One way volunteering may benefit students is through increased service-based learning, a method of teaching wherein students perform and reflect on roles which intersect with their academic curriculum while also addressing community needs. 24 Arguments for adding service roles to curricula are grounded in educational theory, but due to medical school curricula constraints this has not been possible to achieve formally to date.…”
Section: Discussionmentioning
confidence: 99%
“…This will have an immediate bearing on their ability to manage patients once they complete their course. This can also impact their chances of getting employed in near future [ 63 ].…”
Section: Resuming Medical Educationmentioning
confidence: 99%
“…Flexible timings for teaching-learning activities will have to be implemented when medical education resumes in post-COVID times [ 63 ]. Asynchronous learning will also help students to learn at a time of their choice.…”
Section: Resuming Medical Educationmentioning
confidence: 99%